2009
DOI: 10.1007/s00213-009-1700-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mGluR1 antagonism in the dorsal hippocampus on drug context-induced reinstatement of cocaine-seeking behavior in rats

Abstract: RATIONALE The functional integrity of the dorsal hippocampus (DH) is necessary for drug context-induced reinstatement of cocaine seeking. However, the neuropharmacological mechanisms of this phenomenon are poorly understood. OBJECTIVES Given the known significance of group I metabotropic glutamate receptors (group I mGluRs), including the mGluR1 subtype, in drug-induced behaviors, the present study was designed to evaluate the contribution of mGluR1s in the DH to drug context-induced reinstatement of extingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 59 publications
3
68
1
Order By: Relevance
“…Similar to our findings, nicotine-seeking behavior induced by nicotine priming and nicotine-associated cues was attenuated by selective antagonism of mGluR1 in rats (Dravolina et al, 2007). Xie et al (2010Xie et al ( , 2012 also found that blocking mGluR1 activity in the dorsal hippocampus or the nucleus accumbens core inhibited context-induced reinstatement of cocaine seeking. Our results are therefore consistent with recent reports that mGluR1 signaling might play a role in specific neural networks to mediate reactivity to cocaine-associated cues and subsequent relapse to cocaine seeking.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our findings, nicotine-seeking behavior induced by nicotine priming and nicotine-associated cues was attenuated by selective antagonism of mGluR1 in rats (Dravolina et al, 2007). Xie et al (2010Xie et al ( , 2012 also found that blocking mGluR1 activity in the dorsal hippocampus or the nucleus accumbens core inhibited context-induced reinstatement of cocaine seeking. Our results are therefore consistent with recent reports that mGluR1 signaling might play a role in specific neural networks to mediate reactivity to cocaine-associated cues and subsequent relapse to cocaine seeking.…”
supporting
confidence: 90%
“…Regarding psychostimulants, the inhibition of mGluR1 activity blocked cocaineinduced psychomotor sensitization (Dravolina et al, 2006;Kotlinska and Bochenski, 2011) and methamphetamine-induced hyperlocomotion (Satow et al, 2008), and amphetamine-induced locomotor activity was greater in mGluR1 knockout mice compared with their wild-type littermates (Mao et al, 2001). In reinstatement studies, cue-induced reinstatement of cocaine seeking (Xie et al, 2010(Xie et al, , 2012 and nicotine-induced reinstatement of nicotine seeking (Dravolina et al, 2007) were also attenuated by mGluR1 antagonists. In addition, emerging evidence at the molecular level implicates mGluR1 in the regulation of cocaine's long-term effects because it has been shown that the pharmacological manipulation of mGluR1 activity can alter cocaine-induced trafficking of the ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (McCutcheon et al, 2011), which are ligand-gated ionotropic glutamatergic receptors critical for cocaine-induced synaptic plasticity (Tzschentke and Schmidt, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Re-exposure to heroin-conditioned cues results in acute synaptic depression of pyramidal neurons in the ventral mPFC [34] . In addition, the basolateral amygdala is a critical component of the neural circuitry that mediates conditioned and heroin-induced reinstatement of heroin-seeking behavior [35] , and the hippocampus and stimulation of mGluR in the hippocampus are involved in context-induced cocaine-seeking behavior [36,37] . Thus, the blockade of glutamate transmission in the NAc shell by MPEP in the current study supported the role of the glutamatergic projection from the ventral mPFC and amygdala, as well as the hippocampus to the NAc shell in heroin seeking induced by cues or heroin priming.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight hours later, they were surgically implanted with intravenous jugular catheters and 26-Ga stainless steel guide cannulae (Plastics One), aimed bilaterally at the DH (angled laterally by 151; AP À 3.4 mm, ML þ / À 3.1 mm, DV À 2.15 mm). The food training, surgery, and post-operative care procedures have been described previously (Fuchs et al, 2007;Fuchs et al, 2008b;Xie et al, 2010).…”
Section: Food Training and Surgerymentioning
confidence: 99%
“…Hence, in experiments 1, 2, and 4, at least 72 h after the last reinstatement test session, we examined the effects of AP5, PP2, and Ro25-6981 on general locomotor activity and on food-reinforced instrumental motor performance in different subsets of rats (N ¼ 7-8/group), as described previously by Xie et al (2010) and in Supplementary Materials and Methods.…”
Section: Locomotor Activity and Food-reinforced Instrumental Behaviormentioning
confidence: 99%